Youtube sebagai Media Dakwah - Hamdan Hamdan; Mahmuddin Mahmuddin (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:The research carried out this time is library research by tracing various scientific works, in the form of books, papers, journals, magazines that discuss media (especially Youtube) and da'wah and are related to this discussion. The data collection method consists of several stages such as the data collection stage, the data management stage, and the data analysis stage. The subject matter of this research is related to Youtube and da'wah media, Youtube can be a media for da'wah and a model for da'wah on Youtube. The results showed that the use of you tube media as a medium for da'wah was more promising and easier to do. It was said that the relationship between you tube media and da'wah was the same target, the same segmentation and the same needs. Meanwhile, the use of You Tube as a medium of preaching by most famous preachers has used and made the best use of it. The da'wah model on you tube can be in the form of serial video lectures, short video lectures, video lecture pieces, music videos / songs, short story videos and live streaming. The implication of this research is that the preachers and preachers will take advantage of the Youtube media as a media of preaching that is very promising.Abstrak[Indonesia]: Penelitian yang dilakukan kali ini adalah penelitian pustaka dengan melalui penelusuran terhadap berbagai karya ilmiah, berupa buku-buku, makalah, jurnal, majalah yang membahas tentang media (khususnya You Tube) dan dakwah serta ada hubungannya dengan pembahasan ini. Metode pengumpulan data melalui beberapa tahapan seperti tahapan pengumpulan data, tahapan pengelolaan data, dan tahapan analisis data. Pokok bahasan pada penelitian ini adalah terkait dengan media Youtube dan dakwah, Youtube dapat menjadi media dakwah dan model dakwah di Youtube. Hasil penelitian menunjukkan bahwa penggunaan media You Tube sebagai media dakwah semakin menjanjikan dan semakin mudah dilakukan, hal tersebut dikatakan bahwa keterkaitan antara media You Tube dengan dakwah adalah kesamaan sasaran, segmentasi yang sama dan kesamaan kebutuhan. Sedangkan pemanfaatan You tube sebagai media dakwah oleh kebanyakan dai kondang telah menggunakan dan memanfaatkan dengan sebaik-baiknya. Ada pun model dakwah di You Tube dapat berupa video ceramah serial, video ceramah singkat, video potongan ceramah, video musik/lagu, video cerita singkat dan aliran langsung. Implikasi penelitian ini adalah kiranya para dai dan mubalig memanfaatkan media Youtube sebagai media dakwah yang sangat menjanjikan ini.